Increased abundance of actinobacteria and upregulation of primary bile acid biosynthesis in diabetic foot ulcers - Zhou, Mi; Zhang, Han; Zhang, Rui; Wei, Tianshu; Zhou, Xiaojun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundVascular microbial imbalance may disrupt homeostasis and impair wound healing by triggering local and systemic inflammation. Diabetic foot (DF), a severe complication of diabetes, is frequently associated with bacterial infections. However, the arterial microbiota in DF remains unexplored. This study characterizes the arterial microbiota in DF patients and investigates its potential role in disease progression.MethodsA total of 22 patients were recruited, including those undergoing surgery for DF, patients with lower limb atherosclerosis (AS) requiring surgery, and trauma patients who underwent amputation as healthy controls (C). Samples were obtained under sterile conditions, and 16S rRNA sequencing was performed. Microbial diversity and functional pathways were analyzed using QIIME2.ResultsAlpha diversity analysis revealed a progressive decline in microbial diversity from the C group to the AS and DF groups. Beta diversity analysis demonstrated that the DF and AS groups clustered closely, while both exhibited significant microbial compositional differences compared to the C group (ANOSIM, P < 0.01). At the phylum level, Actinobacteria was significantly enriched in the DF and AS groups, whereas TM6 was reduced in the DF group and Proteobacteria was reduced in the AS group. LEfSe analysis identified Corynebacterium, Streptophyta_Group, Caulobacter, Hydrogenophaga, and Diaphorobacter as key representative genera in the DF group. Furthermore, KEGG analysis revealed metabolic alterations in both the DF and AS groups, including upregulated metabolism and organismal system pathways. At level 3, the DF group exhibited significant downregulation of amino sugar and nucleotide sugar metabolism, whereas primary bile acid biosynthesis was markedly upregulated, suggesting a potential role in DF progression.ConclusionDF is associated with distinct alterations in arterial microbiota composition and metabolic pathways. Alterations in Actinobacteria and primary bile acid biosynthesis may be relevant to DF progression and could serve as potential therapeutic targets.